Isolation and Elucidation Structure of 28-Hydroxy-3-Friedelanone of Nyamplung (Callophyllum inophyllum, Linn.) Leaves - Triana Kusumaningsih; Muhammad Widyo Wartono; Nais Puji Wijanarti (The Journal of Pure and Applied Chemistry Research, 2020)
The isolation triterpenoid from Nyamplung (Callophyllum inophyllum, Linn.) leaves has been conducted. The isolation was employed by maceration using ethanol as solvent and liquids extraction using ethyl acetate. Ethyl acetate extract was partitioned successively using nonpolar solvent with hexane, dichloromethane, and diethyl ether, respectively. The diethyl ether extract was purified by column chromatography. The isolated compound of fraction D1 was obtained as white solids crystal with yield of 0.0035%. The isolated compound was determined based on the FTIR, 1HNMR, 13CNMR, HSQC, and HMBC spectra. The isolated compound was identified as 28-hydroxy-3-friedelanone.